(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The rapid digital development of healthcare systems and contemporary globalization necessitate a fundamental re-evaluation of the content, methods, and outcomes of medical education. Traditional knowledge-oriented educational models are insufficient for developing the complex competencies required in modern clinical practice, particularly clinical reasoning, timely and evidence-based decision-making, and professional adaptability. This article analyzes the theoretical and methodological foundations of competency-based education within the framework of the digital transformation of medical education and highlights its role in fostering clinical reasoning and preparing a sustainable professional workforce. The impact of digital learning platforms, simulation-based technologies, and integrated educational environments on educational effectiveness is discussed. The findings demonstrate that aligning competency-based education with digital tools provides a robust methodological basis for enhancing the quality of clinical training, strengthening the integration of education and practice, and preparing healthcare professionals who meet the evolving needs of healthcare systems.